PENGARUH PENGEMBALIAN KREDIT NASABAH TERHADAP KINERJA KEUANGAN PADA KOPERASI SERBA USAHA SORAYA KOTA PAKPAKBARAT TAHUN 2014-2018 - LUNA THERESIA TAMBUNAN (LP2MTBM MAKARIOZ, 2020)
Co-operative is a legal entity established by an individual or cooperative legal entity, with the separation of the wealth of itsmembers as capital to run the business, which meets the aspirations and common needs in the economic, social, andcultural fields in accordance with the values and principles of the cooperative. There is a positive effect of credit returns onfinancial performance. So that if the number of member loans increases then the Financial Performance increases. Theamount of credit refund at Koperasi Serba Usaha (KSU) soraya Pakpakbarat every year. There was a significant positiveinfluence on the interaction between credit edifices and financial performance of 62.5 while the rest was influenced by othervariables not included in the research model.